2013
DOI: 10.1089/apc.2012.0388
|View full text |Cite
|
Sign up to set email alerts
|

Disclosure, Knowledge of Partner Status, and Condom Use Among HIV-Positive Patients Attending Clinical Care in Tanzania, Kenya, and Namibia

Abstract: We describe the frequency of and factors associated with disclosure, knowledge of partner's HIV status, and consistent condom use among 3538 HIV-positive patients attending eighteen HIV care and treatment clinics in Kenya, Namibia, and Tanzania. Overall, 42% of patients were male, and 64% were on antiretroviral treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
54
3

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(70 citation statements)
references
References 37 publications
(48 reference statements)
13
54
3
Order By: Relevance
“…Our study showed evidence of an inverse association between disclosure and unprotected sex, consistent with previous research in this population [37][38][39][40] and consistent with the disclosure processes model that suggests disclosure influences perceptions of risk. Some HIV-infected adults may consider disclosing their serostatus to be a means of transferring responsibility for HIV prevention efforts (e.g., condom use) to their partners.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Our study showed evidence of an inverse association between disclosure and unprotected sex, consistent with previous research in this population [37][38][39][40] and consistent with the disclosure processes model that suggests disclosure influences perceptions of risk. Some HIV-infected adults may consider disclosing their serostatus to be a means of transferring responsibility for HIV prevention efforts (e.g., condom use) to their partners.…”
Section: Discussionsupporting
confidence: 91%
“…The model also included a set of potential confounding variables (age, time since HIV diagnosis, and partner HIV serostatus) selected based on their associations with both HIV serostatus disclosure and unprotected sex in previous studies. 26,37,43,46,47 We followed the strategy of testing the global hypothesis of no interaction first. If interactions were present, the plan was to use the predicted probabilities to examine the disclosure effect by sexual behavior groups.…”
Section: Statistical Analysesmentioning
confidence: 99%
See 1 more Smart Citation
“…Although disclosure rates to family or friends was lower in our study than that reported in one study in East Africa [19], the distribution of disclosure rates was similar, with people disclosing their HIV status most easily to their siblings, then to their mother, children, father and, finally, to friends [19]. We found that disclosure to relatives was more frequent for females, which is consistent with previous work [4,20,21].…”
Section: Discussionsupporting
confidence: 88%
“…Rates of knowledge of a steady partner's serostatus was also very different between individuals who had disclosed (79 %) and those who had not (31 %). Disclosure to a steady partner should be encouraged since on the one hand it enables the couple to make joint decisions on how to protect their health, including condom use [19], and on the other hand increases HIV testing and reduces the burden of undiagnosed HIV.…”
Section: Discussionmentioning
confidence: 99%